Interleukin-17–induced neutrophil extracellular traps mediate resistance to checkpoint blockade in pancreatic cancer - Zhang, Yu; Chandra, Vidhi; Riquelme Sanchez, Erick; Dutta, Prasanta; Quesada, Pompeyo R.; Rakoski, Amanda; Zoltan, Michelle; Arora, Nivedita; Baydogan, Seyda; Horne, William; Burks, Jared; Xu, Hanwen; et al. (The Journal of experimental medicine, 2020)
Pancreatic ductal adenocarcinoma (PDAC) remains a lethal malignancy with an immunosuppressive microenvironment that is resistant to most therapies. IL17 is involved in pancreatic tumorigenesis, but its role in invasive PDAC is undetermined. We hypothesized that IL17 triggers and sustains PDAC immunosuppression. We inhibited IL17/IL17RA signaling using pharmacological and genetic strategies alongside mass cytometry and multiplex immunofluorescence techniques. We uncovered that IL17 recruits neutrophils, triggers neutrophil extracellular traps (NETs), and excludes cytotoxic CD8 T cells from tumors. Additionally, IL17 blockade increases immune checkpoint blockade (PD-1, CTLA4) sensitivity. Inhibition of neutrophils or Padi4-dependent NETosis phenocopies IL17 neutralization. NMR spectroscopy revealed changes in tumor lactate as a potential early biomarker for IL17/PD-1 combination efficacy. Higher expression of IL17 and PADI4 in human PDAC corresponds with poorer prognosis, and the serum of patients with PDAC has higher potential for NETosis. Clinical studies with IL17 and checkpoint blockade represent a novel combinatorial therapy with potential efficacy for this lethal disease.